GEOMORPHOLOGICAL CLASSIFICATION AND LANDFORMS INVENTORY OF THE MIDDLE-ATLAS VOLCANIC PROVINCE (MOROCCO): SCIENTIFIC VALUE AND EDUCATIONAL POTENTIAL - Amine, Abdelmounji; El Amrani El Hassani, Iz-Eddine; Remmal, Toufik; El Kamel, Fouad; Van Wyk de Vries, Benjamin; Boivin, Pierre (Quaestiones Geographicae, 2019)
Through the tabular morphology of northwestern part of the Middle-Atlas in Morocco, numerous uncovered monogenetic volcanoes arise structured of pyroclastic product layers and lava flows. Our fieldwork results witness a wide-ranging volcanic shape spectrum, as cones, maars, tuff-rings, and cone-maar mixes, generally associated with a later lava flow discharge that could develop many surfaces and appearances. There are withal sundry eruptive products such as pahoehoe lava, scoria, tuff, lapilli, peperites, base-surges, bombs, etc. This monogenetic volcanic field of practically 1000 km2 offers remarkable eruptive landforms, referred to as the largest, and the youngest volcanic field in Morocco, which consists of a large area within the Ifrane National Park. This fieldwork study provides a renewed volcanic geomorphological classification table and GIS data to be used by a wide public range for both educational and geo-touristic interest and access effectively to such a high-mountain natural museum. In the event that these volcanic structures were appropriately dealt with, the high educational scientific content and the notable touristic vocation would almost certainly create business openings and new financial wages for neighborhood populaces. This work focuses to share our outcomes and emphases the scientific value about the monogenetic volcanic field around the tabular Middle-Atlas in Morocco.